The Legal Character of a Tax Audit in Functional Aspect - Szczepańska, Magdalena (Journal of Finance and Financial Law, 2014)
Article discuss the legal nature of a tax audit procedure with regard to the concept of the function of the law. The text analyzes the position of tax audit procedure in the context of other tax procedures provided for in the Tax Code. Article also refers to the functional concept of the construction of the Tax Code considering the location of a tax audit in the proposed system. The author justifies the need to extract a tax audit as a stand-alone procedure and proposes some directions of change within the institution.